Variability of winds in X-ray binaries - Trigo, M.; Boirin, L.; Migliari, S.; Miller-Jones, James; Parmar, A.; Sidoli, L. (2012)
We discuss the variability of winds in two low-mass X-ray binaries, GX 13+1 and 4U 1630-47. XMM-Newton observations of these sources show that strong, photoionised winds with column densities well above 1022 cm -2 can be present in both neutron star and black hole LMXBs. Such winds can fade significantly due to changes in the flux or spectral hardness of the continuum. In particular, a decrease of column density and/or an increase of ionisation are measured when the flux increases or the spectrum hardens. We show how variability studies can help us to understand what triggers changes in the wind and discuss the limitations of current instruments for such studies.